Studi Optimalisasi Fasilitas Parkir di Fakultas Keguruan Ilmu Pendidikan (FKIP) Universitas Lampung - Yuda, Maulana Rendri; Sulistyorini, Rahayu; Herianto, Dwi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
This study consisted of two phases, which collects data required parking, such as license platenumbers of vehicles, to enter and exit the vehicle, and then analyze it with some formula that isused as a parameter conclusion. This study uses several parameters that are used as a referenceconclusion and settlement of the problem, namely the accumulation of vehicle parking, parkingindex, duration of parking, parking capacity, as well as parking turnover rate (PTO). From thecalculation results will be concluded and related solutions in that Faculty.From the analysis, the accumulated value obtained in FKIP largest car park as many as 54vehicles, while the majority of motor vehicle accumulation of 869. In calculating the capacity ofthe car park at FKIP obtained the largest parking capacity as many as 557 vehicles, while formost motor vehicle parking capacity that is equal to 6361 vehicles. In parking index calculationindex values obtained for the vehicle's biggest car park as many as 125,81%, while the largestmotor vehicle as much as 114,49%. At the turn of the calculation in the FKIP-level parking forautomobiles obtained maximum value of 3,79, while in a motor vehicle obtained maximumparking turnover rate of 3,64. From calculations conclude that the motor vehicle parking area atFKIP could not accommodate vehicle parking. As a solution to the problem of the parking lot,then made plans car and motor vehicle parking area at the FKIP plan that can accommodatevehicles parked cars on the faculties.Keywords : FKIP, parking index, parking duration , parking capacity, PTO